Sociaal isolement bij ouderen: een typologie als richtlijn voor effectieve interventies - Anja Machielse (Journal of Social Intervention: Theory and Practice, 2011)
Social isolation in older people: a typology as guide for effective interventions In the Netherlands many interventions are implemented to reduce or prevent social isolation amongst older people, but most interventions appear to have little effect. Interventions to combat or solve social isolation face some important problems. The main problem is the heterogeneity of the socially isolated. This article provides insight in this heterogeneity by means of a typology of eight types of socially isolated people. The typology may serve as a tool for defining appropriate interventions and guidance. It shows that the time investment and the intensity of the intervention can vary significantly. The typology also shows what results can be achieved and what the limits of what can be achieved by social professionals are.. For certain types, isolation can be counterbalanced or removed. For other types, results can be achieved within the field of practical problem-solving. Sometimes, it is not possible to improve the situation. In those cases, creating a safety net to prevent further escalation of the situation is the last alternative.